PENGARUH INFLUENCER ENDORSEMENT DAN ONLINE CUSTOMER REVIEW TERHADAP PURCHASE INTENTION PADA KLINIK KECANTIKAN ELLA SKINCARE DENGAN TRUST SEBAGAI VARIABEL INTERVENING - Faraliza Gibranty Syarifudin; Nur Achmad (JURNAL LENTERA BISNIS, 2024)
The purpose of this study was to analyze the effect of influencer endorsement and online customer reviews on purchase intention at the Ela skincare beauty clinic with trust as an intervening variable. This research uses quantitative methods. The population in this study were students throughout Solo Raya who knew, had bought, and used Ella Skincare products. The number of samples used was 384 respondents. The sampling technique used a non-probability sampling approach with purposive sampling technique. This study uses primary data obtained by filling out a questionnaire distributed to respondents via google form. The data analysis technique used in this research is descriptive analysis and Structural Equation Model (SEM) analysis with Smart Partial Least Square (PLS). The results of this study are Influencer endorsement, Online customer and Trust have a positive and significant influence on purchase intention. Influencer endorsement and online customer review have a positive and significant influence on trust. Influencer endorsement has a positive and significant influence on purchase intention which is mediated by trust. Online customer reviews have a positive and significant influence on purchase intention which is mediated by trust. Keywords: Influencer endorsement, Online customer, Purchase intention, Trust.